Systematic Review And Meta-Analysis: Diabetes Mellitus In Dachshund Dogs - Adil, Aftab; Prasad, Anupa; Kumar, Amit (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus (DM) is a chronic endocrine disorder in dogs characterized by persistent hyperglycemia due to insulin deficiency. While canine DM generally resembles type 1 diabetes in humans, certain breeds—including the Dachshund—exhibit a higher predisposition due to a combination of genetic, hormonal, and environmental factors [1, 2, 8]. Objective: To systematically evaluate the prevalence, clinical presentation, risk factors, management strategies, and outcomes of diabetes mellitus in Dachshund dogs, and to assess the implications for clinical practice and future research. Methods: A comprehensive literature search was conducted across PubMed, ScienceDirect, Scopus, and Google Scholar for articles published between 2000 and 2024. Keywords included "diabetes mellitus in dogs," "canine diabetes," "Dachshund diabetes," and "breed predisposition to diabetes." Studies involving breed-specific data on Dachshunds were included, while general canine DM reports lacking breed-specific outcomes were excluded. Extracted data covered prevalence rates, clinical signs, hormonal and genetic influences, treatment protocols, and therapeutic outcomes [2, 7]. Results: Dachshunds account for approximately 3.2% of canine diabetes cases in breed-specific studies, with an odds ratio of 1.6 for developing DM compared to mixed-breed dogs [2]. Middle-aged to older intact females are particularly at risk due to progesterone-induced insulin resistance during diestrus [1, 6]. Key clinical signs include polyuria, polydipsia, weight loss, cataracts, and lethargy [5, 7]. Chronic pancreatitis and obesity are major contributing factors [4, 8]. Standard treatments involve insulin therapy, dietary regulation, and owner monitoring [10]. With proper care, affected dogs can achieve good glycemic control and prolonged quality of life, though complications such as cataracts and diabetic ketoacidosis remain concerns [5, 10]. Conclusion: Diabetes mellitus in Dachshunds is a manageable but lifelong condition influenced by complex genetic and physiological factors [1, 3, 5]. Early detection, hormonal management (spaying), weight control, and owner education are essential [6, 7]. Further breed-specific genomic research is warranted to enhance preventive strategies and improve outcomes in this predisposed population [3, 5].